Thermodynamic modeling of the behavior of Uranium and Arsenic in mineralized Shaazgai-Nuur Lake (Northwest Mongolia); Doklady Earth Sciences; Vol. 465, iss. 1 - Gaskova O. L. Olga; Isupov V. P. Vitaly; Vladimirov A. G. Alexander; Shvartsev S. L. Stepan Lvovich; Kolpakova M. N. Marina Nikolaevna (2016, 2016)
Title screen